Pelatihan penggunaan aplikasi Mendeley bagi mahasiswa Sekolah Tinggi Ilmu Pembangunan Indonesia (STIE-PI) Makassar dalam penulisan karya ilmiah - Muhammad Imam Ma’ruf; Sri Astuty; Andi Samsir; Amar Basra; M. Fadhil Albi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Partners of the Community Partnership Program (PKM) are students of Sekolah Tinggi Ilmu Ekonomi Pembangunan Indonesia (STIE-PI) Makassar. The problem is the lack of understanding of students in reference writing when writing a thesis / final project. Generally, students do not know the difference between reference writing and citation style. The used method are lecture, question and answer, simulation, and practice. The achieved results were students able to use the Mendeley application as a reference management software and academic social network and in reference writing.